Child Maltreatment Fatality Review: Purposes, Processes, Outcomes, and Challenges. (December 2021) - McCarroll, James E.; Fisher, Joscelyn E.; Cozza, Stephen J.; Whalen, Ronald J.
Better understanding of the causes and circumstances of maltreatment deaths of children is needed to prevent tragedy. The purpose of this article is to facilitate understanding of child maltreatment fatality review processes and their outcomes. A literature review was conducted through searches of the databases PubMed, PsycINFO, and EMBASE and through citations in publications. Over 165 publications were reviewed and 55 were selected for inclusion. Papers were from the United States, England, Ireland, Northern Ireland, Netherlands, France, Canada, Australia, South Africa, Switzerland, Saudi Arabia, Japan, and China. These were included if they described fatality review goals, authority, procedures, and outcomes. Although we searched databases on a continual basis during the preparation of this review, we could have missed publications, particularly those in newspapers and journals that are not included in large-scale databases or cited in other articles. Improvement of fatality review requires diligence by individuals and organizations that provide information to the reviewers. Among challenges to the review process are varying criteria for review, misclassifications of the manner of death, inadequate or incomplete forensic and medical investigations, lack of information about the perpetrator, diversity of the community, concealment of the cause of death by parents or other caregivers, and disagreement among reviewers about the results of their inquiries. Institutional challenges are also present, which include the need for funding, privacy issues on obtaining information, updating reviewer training, lack of follow-up by institutional authorities on the recommendations of the reviews, and research facilitating the review of maltreatment fatalities.